2012
DOI: 10.1088/0004-637x/762/1/56
|View full text |Cite
|
Sign up to set email alerts
|

ALBEDO PROPERTIES OF MAIN BELT ASTEROIDS BASED ON THE ALL-SKY SURVEY OF THE INFRARED ASTRONOMICAL SATELLITEAKARI

Abstract: We present an analysis of the albedo properties of main belt asteroids detected by the All-Sky Survey of the infrared astronomical satellite AKARI. The characteristics of 5120 asteroids detected by the survey, including their sizes and albedos, were cataloged in the Asteroid Catalog Using AKARI (AcuA). Size and albedo measurements were based on the Standard Thermal Model, using inputs of infrared fluxes and absolute magnitudes measured at optical wavelengths. Main belt asteroids, which account for 4722 of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 65 publications
3
53
0
1
Order By: Relevance
“…where p V is the geometric albedo. Assuming an albedo of 0.098 ± 0.081 for the X-type (Usui et al 2013), the effective diameter and range were found to be 8 m and 6 m < D < 20 m, respectively. Since Mainzer et al (2011b) also showed the albedo of 0.099 ± 0.161 for Tholen X-complex class and the albedo of 0.111 ± 0.143 for Bus-DeMeo X-complex class, the assumption of ∼0.1 for the X-type albedo was reasonable.…”
Section: Taxonomic Class and Diametermentioning
confidence: 98%
“…where p V is the geometric albedo. Assuming an albedo of 0.098 ± 0.081 for the X-type (Usui et al 2013), the effective diameter and range were found to be 8 m and 6 m < D < 20 m, respectively. Since Mainzer et al (2011b) also showed the albedo of 0.099 ± 0.161 for Tholen X-complex class and the albedo of 0.111 ± 0.143 for Bus-DeMeo X-complex class, the assumption of ∼0.1 for the X-type albedo was reasonable.…”
Section: Taxonomic Class and Diametermentioning
confidence: 98%
“…For both scenarios, we assumed an inclination of 60 • (the median value for an isotropic distribution of inclinations) and a Bond albedo of 0.1 (a typical value for rocky bodies; Usui et al 2013). Physically realistic atmospheres would likely have a higher albedo (e.g., Earth's albedo is 0.3).…”
Section: Predicted Thermal Phase Variationmentioning
confidence: 99%
“…Although thermal infrared data of Phaethon exist that allowed determining a radiometric diameter (Green et al 1985;Tedesco et al 2002;Usui et al 2011Usui et al , 2013, there is currently no estimate available for the thermal inertia for this body.…”
Section: Introductionmentioning
confidence: 99%